The Journal of the Acoustical Society of Japan (E) - GUBRYNOWICZ, Ryszard (Archives of Acoustics, 1981)
With real satisfaction we welcome the English version of periodical of the Acoustical Society of Japan, The Journal of the Acoustical Society of Japan (E).